Documentación de vivencias recreativas de un grupo de mujeres de Los Cuadros mediante Fotovoz - Salazar Salas, Carmen Grace; Juniu, Susana (Universidad de Costa Rica, 2019)
This study is part of a research project that includes four vulnerable communities. This article presents the results of the first community. The purpose of this qualitative investigation is to examine through Photovoice the recreation experiences of a group of women from Los Cuadros of Purral, in Goicoechea, San José, Costa Rica, as well as the contextual factors that facilitated or inhibited their recreational participation. This technique consists of giving voice to people through photographs and narratives to document their reality. The participants were selected by convenience. The six women photographed their community to document their environment and recreational circumstances. The women wrote a paragraph explaining what each photography represented. The participants worked in groups to analyze and categorized the photos into topics and chose the ones that best represented each theme. The results showed five themes and 24 subthemes. Two of the five themes (Support received from the government and private enterprise, and Sense of community/community organization) were factors that enhanced recreation, other two themes (Disappointment due to negative factors, and Manipulation of poverty) were factors that hindered it, and the fifth theme was related to the recreational activities carried out in the community. The main conclusions involve the empowerment of women because they felt acknowledged for their opinions, the appreciation of recreation, and the recognition that the facilities and the recreational offer are not the required to obtain the benefits that recreation provides.